Methicillin-Resistant Staphylococcus aureus: A Public Health Issue with Economic Consequences - Mireille Goetghebeur; Pierre-Alexandre Landry; Donald Han; Colin Vicente (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) has become endemic worldwide in hospitals, and community-associated MRSA is spreading into the community at large.